THE USE OF COMMUNICATIVE LANGUAGE TEACHING TO INCREASE THE STUDENTS’ MOTIVATION - Achmad Basir; Andi Tenri Ampa; Sulfasyah Sulfasyah (Universitas Muhammadiyah Makassar, 2021)
This research aimed to improve the students’ motivation by using Communicative Language Teaching (CLT) Method in teaching English at the Third Semester of Dental Nurse Department Poltekkes Kemenkes Makassar. The teaching material was English for Specific Purposes and the subjects of the research consisted of two classes, they were class A as a control class and class B as an experimental class. This research used quasi-experimental design with nonequivalent control group design. The research indicated significant increasing of the students’ English learning motivation by using Communicative Language Teaching method for experimental class than applying Grammar Translation Method in control class. The score of Intrinsic, Integrative and Instrumental motivation, indicated it. The mean scores of students before treatment was 47.05 and after treatment was 81.78 in experimental, while in control class mean scores of students was 51.16 and after treatment was 51.89. The results of the research showed that Communicative Language Teaching (CLT) was effectively improving the students’ English Learning Motivation than using Grammar Translation Method (GTM). The table shows the different students’ mean score for both two Classes. For Experimental class, the students’ mean score improved significantly from 47.05 with standard deviation 7.491 to 81.78 with standard deviation 6.386. For Control class, the mean score of the students increase from 51.16, standard deviation 10.602 to 51.89, standard deviation 10.671.